CHARACTERISTICS OF PRELIMINARY RIGHTS FOR INSURED IN GETTING REPAYMENT OF LOSSES ON BANKRUPT INSURANCE COMPANIES - Fani Martiawan Kumara Putra (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2017)
In the business world and all its competition, debt is not a bad thing for businesses whether small, medium, or even large businesses, as long as the debt can still be paid back. A company is also not immune to the events of debts, and the accounts of these debts are companies called solvable, which means they are able to pay their debts, there is also a company called insolvency, which means the company is unable to pay its debts. For companies that cannot afford to pay their debts, the law has provided instruments for settlement, among others, can follow the rule of law guarantees, or the rule of bankruptcy when the conditions are met. Both of these instruments have their own characteristics. Based on the bankruptcy law, the debtor who is determined to be bankrupt will become ineligible for his property until the bankruptcy is over, also not for the insurance company. Insurance companies that have decided bankruptcy will experience payment constraints for the insured party filing a claim, especially when it is not based on the existence of norms or understanding of good norms. This research is a normative study. The results obtained in this study are the insured party can still get the rights through his claim, and its nature can precede with certain conditions.